Brass products in the coronet excavated from an M2-numbered Sui-Tang-dynasty tomb situated in Kun Lun Company in Xi'an, Shaanxi - Yanbing Shao (SpringerOpen, 2021)
Abstract Ancient Chinese brass smelting technology has promoted the invention of zinc smelting, thus becoming an important part of the metallurgical history. However, the information concerning its origin and development is still controversial. In that regard, thorough analysis of composition and structure of the early brass is crucial for studying various stages of the ancient brass smelting technology history. This study aimed to investigate brass artifacts from Kunlun M2 tomb in Xi'an, Shaanxi, dating back during Sui to early Tang Dynasty (581–712 AD). The composition and metallographic characterization of the materials was performed using XRF, SEM–EDS and metallographic analysis. According to the results, brass was composed of 83 wt% of copper, 12 wt% of zinc, and 3 wt% of tin. Furthermore, its microstructure consisted of α-isometric single crystals with some slip lines and a few twinned grains. This indicated that brass was obtained by melting an appropriate mixture of zinc ores and copper ores at a temperature above 920 °C. Furthermore, brass support components were installed on the coronet after integral hot forging and partial cold shaping. Besides, the use of brass in the coronet was in conformity with the social hierarchy of that historical period, and also reflected the attention paid to the properties of materials.